Meeting places: drivers of change in Australian Aboriginal cultural institutions - Jones, Tod; Birdsall-Jones, Christina (Routledge, 2014)
Since the 1970s, there has been a fraught yet hopeful Aboriginal cultural resurgence in Australia. An element of this movement has been the establishment of Aboriginal art centres and cultural centres across Australia. Using a comparative approach to Aboriginal art centres, this paper analyses the appearance and characteristics of the more recent Aboriginal cultural centres. The methods used are a review of the literature on Aboriginal art centres, and for the less-researched Aboriginal cultural centres, a case study. This paper posits that cultural centre characteristics are shaped through the formation of alliances made possible by the advent of land rights, an Aboriginal cultural turn amongst Aboriginal and non-Aboriginal people, and changing approaches to regional development. While not themselves a movement that will lead to socio-economic change, these types of arts and heritage projects are aligned to such movements. With a larger scale and more central locations, Aboriginal cultural centres open up opportunities for larger and more diverse alliances, and therefore new opportunities for Aboriginal people’s participation, activism and expression.